345 HOW PREVALENT ARE UNDETECTED DEPRESSIVE SYMPTOMS AMONGST OLDER HOSPITAL INPATIENTS?. (25th October 2022) - Chambers, H; Ahmed, R; Cloonan, J; May, E; Madden, R; Briggs, R
Abstract: Background: Depression in later life can have a profound effect on quality of life, functional independence, healthcare use and early mortality. For multiple reasons however, depression in later life may often go undetected. The aim of this study is to ascertain the point prevalence of depressive symptoms on a specialist geriatric medicine unit, examining the rate of detection of clinically significant symptoms. Methods: The study site is a large urban university teaching hospital with a 150-bed specialist geriatric medicine unit, comprising acute medical, rehabilitation and long-stay wards. Depressive symptoms were assessed using the Centre for Epidemiological Studies Depression Scale (CES-D) with a score ≥16 indicating significant symptoms. Medical notes were examined for documentation of screening for/assessment of depression since admission. Patients were included if they were aged ≥70 years, a current inpatient and able to give informed consent. Results: Almost 62% (47/76) of the study sample (Mean age 83 years, 66% female) met criteria for significant depressive symptoms. Almost-half (23/47, 49%) of patients with significant depressive symptoms were screened for depression (either with a structured screening tool, a documented mood assessment or review by psychiatry) while in hospital. The mean length of stay for patients with depressive symptoms who had not yet been screened for depression was 42.7 (23.2 – 62.2) days and over 70% had been in hospital for at least 10 days, with almost two-thirds (15/24, 65%) currently residing on an acute geriatric medicine ward (rather than a rehabilitation or long stay ward). Conclusion: Our study demonstrates a high burden of depressive symptoms amongst older inpatients, with almost 2 in 3 meeting criteria for clinically significant symptoms. Less than half of those with clinically significant symptoms were screened for depression however, representing an important missed opportunity to identify, and possibly treat, depression.